The Changing Face of Open Source. - Lawton, George (Computer (00189162), 2009)
The article discusses the acceptance of open source software development methods by the mainstream software industry as of 2009. The tendency for some open source software companies to adopt business models that are closer in appearance to commercial software companies is mentioned. The acceptance of open source methods by mainstream companies such as Hewlett-Packard and IBM is noted. Also mentioned is the opposition of some members of the open source software industry to such developments, noting that John Sullivan of the Free Software Foundation believes that software should always be open source and free to use, distribute, and change without restrictions.